Draft genome sequence of the feruloyl esterase-producing strain lactobacillus fermentum CRL1446, a probiotic for malnutrition - Abeijon Mukdsi, Maria Claudia (2018)
We report here the draft genome sequence of Lactobacillus fermentum CRL1446 (2,148,781 bp, 51.4% G+C content). This strain exhibits feruloyl esterase activity and important technological and probiotic properties. Because of its proven beneficial effects in vivo, it represents an interesting candidate for the development of functional foods or pharmabiotics for malnutrition.